Cooperating embedded systems and wireless sensor networks - Banatre, Michel, 1950- (London : ISTE, 2008)
'A number of different system concepts have become important in the broader context of embedded systems over the past few years. Whilst there are some differences between them, this book argues that in fact there is much they share in common, particularly the important notions of control, heterogenity, wireless communication, dynamics/ad hoc nature and cost.''The first part of the book covers cooperating object applications and the currently available application scenarios, such as control and automation, healthcare, security and surveillance.''The second part discusses paradigms for algorithms and interactions. The third part covers various types of vertical system functions, including data aggregation, resource management and time synchronization. The fourth part outlines system architecture and programming models, including all currently available architecture models and middleware approaches that can be used to model the complexity of cooperating object technology. Finally, the book concludes with a discussion of the trends guiding current research and gives suggestions as to possible future developments and how various shortcomings in the technology can be overcome.'--BOOK JACKET.
An introduction to the concept of cooperating objects and sensor networks / Anibal Ollero, Adam Wolisz, and Michel Ban{u3874}re -- Applications and application scenarios / {u3962}nem Baydere ... [et al.] -- Paradigms for algorithms and interactions / Andrea Zanella ... [et al.] -- Vertical system functions / Marcelo Pias ... [et al.] -- System architectures and programming models / S. Santini ... [et al.] -- Cooperating objects roadmap and conclusions / Pedro JosMarr, Daniel Minder, and the Embedded WiSeNts Consortium.
Includes bibliographical references and index.
Keywords: Embedded computer systems; Sensor networks